A new hot-rolled lightweight steel with ultra-high strength and good ductility designed by dislocation character and transformation strain. (15th April 2022) - Song, Chenghao; Wang, Haoliang; Sun, Zhenzhong; Xu, Juping; Chen, Huaican; Yin, Wen
Abstract: The method of Si substituting for Al was proposed to design a novel hot-rolled lightweight steel with ultra-high ultimate tensile strength (2046 MPa) and good total elongation after fracture (7.4%). The good ductility mainly originates from high screw dislocation fraction and transformation strain of retained austenite due to Si addition. This work breaks the impression of Si making steel brittle and deteriorate for many years and opens up a new route for alloy design through adjusting dislocation character and transformation strain.